2011
DOI: 10.1080/09593330.2010.501822
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of TiO2and TiO2–Pt and their application in the removal of Cr (VI)

Abstract: The deposition of noble metal on titanium dioxide (TiO2) has been considered as an effective strategy to improve the activity of TiO2. In this paper, TiO2 nanoparticles were prepared via a sol-gel route, followed by heat treatment at elevated temperatures. TiO2-Pt catalyst was prepared by deposition of platinum (Pt) on the surface of as-prepared TiO2 nanoparticles. TiO2 and TiO2-Pt were characterized by X-ray diffraction, transmission electron microscopy, Raman spectroscopy, ultraviolet-visible differential re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Cr(VI) exists in the aqueous solution as Cr 2 O 7 2− . The significantly increased H + concentration would assist the Cr 2 O 7 2− in trapping electrons and therefore favors the reduction of Cr(VI) [27,28]. Moreover, the produced Cr(III) reduced from Cr(VI) would possibly attach on the surface of catalyst as Cr(OH) 3 under alkaline condition, which covers the active sites of catalyst and hinders to some extent the photocatalytic reaction.…”
Section: Photocatalytic Performances Of Ag-ag 2 S/tio 2 For the Photomentioning
confidence: 97%
“…Cr(VI) exists in the aqueous solution as Cr 2 O 7 2− . The significantly increased H + concentration would assist the Cr 2 O 7 2− in trapping electrons and therefore favors the reduction of Cr(VI) [27,28]. Moreover, the produced Cr(III) reduced from Cr(VI) would possibly attach on the surface of catalyst as Cr(OH) 3 under alkaline condition, which covers the active sites of catalyst and hinders to some extent the photocatalytic reaction.…”
Section: Photocatalytic Performances Of Ag-ag 2 S/tio 2 For the Photomentioning
confidence: 97%
“…The photocatalyst of TiO 2 deposited by platinum (TiO 2 -Pt, 1 wt%) was prepared as follows (Fan et al, 2009;Fan et al, 2011): 1) The prepared TiO 2 was distributed in water by means of an ultrasonic apparatus; 2) Excessive methanol and a certain amount of H 2 PtCl 6 were added into the TiO 2 suspension; 3) The pH of this suspension was adjusted to 3.0 by adding NaOH and HClO 4 ; 4) The suspension was magnetically stirred in the dark for approximately 1 hour prior to irradiation to achieve an adsorption-desorption equilibrium. During this process, N 2 was pumped into the suspension; 5) The suspension was irradiated by UV light (120 W) for 5 hours; 6) The suspension sample was filtered, washed, and dried.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Special attention has been focused on doping TiO 2 -based materials with noble elements. [16][17][18][19][20][21] Study revealed that Ag dopant accelerates the transformation of anatase TiO 2 to its rutile form, and relatively low Ag concentration (2-5%), results in increase in specific surface areas of the TiO 2 powders. [22] The presence of Ag in crystalline TiO 2 was found to strongly enhance the photocatalytic activity of TiO 2 in various degradation processes.…”
Section: Introductionmentioning
confidence: 98%